DETERMINAN MINAT MENGGUNAKAN APLIKASI REKSA DANA BIBIT PADA MAHASISWA - Aliyah, Safa; Medyawati, Henny; Yunanto, Muhamad (Universitas Multimedia Nusantara, 2023)
Abstract- The purpose of this research was to analyze the effect of perceived ease of use, trust and product knowledge on interest in using the Aplikasi Reksa Dana Bibit on students/I Gunadarma University Faculty of Economics 2018. This research will also find the most dominant in the research model. The source of the data for this research is primary data obtained with a questionnaire instrument distributed via google form. The data in this study were successfully collected as many as 100 respondents who were valid and reliable. The test stages carried out in this study were: validity test, reliability test, normality, heteroscedasticity, multicollinearity, multiple linear regression, multiple linear coefficients, coefficient of determination, f test and t test were used to test the hypothesis. The sampling method in this study is non-probability sampling with purposive sampling technique.The results of this research is the variable perceived ease of use, trust and product knowledge had an effect on interest in using the Aplikasi Reksa Dana Bibit. The most dominant variable in this study was the product knowledge variable. Keywords: Aplikasi Bibit; Kepercayaan; Minat menggunakan; Persepsi Kemudahan Penggunaan; Pengetahuan Produk